High‐molecular‐weight kininogen cleavage correlates with disease states in the bradykinin‐mediated angioedema due to hereditary C1‐inhibitor deficiency. Issue 12 (December 2014) - Suffritti, C.; Zanichelli, A.; Maggioni, L.; Bonanni, E.; Cugno, M.; Cicardi, M.
Summary Background The inherited deficiency of C1‐inhibitor (C1‐INH), which can be quantitative (type I) or qualitative (type II), is characterized by recurrent attacks of oedema, and it is known as hereditary angioedema due to C1‐INH deficiency (HAE‐C1‐INH). The frequency of symptoms varies widely among patients and in the same patient during life. Objective To identify laboratory markers of disease severity in HAE‐C1‐INH patients. Methods We studied 162 patients with differently severe HAE‐C1‐INH during remission, 31 HAE‐C1‐INH patients during attacks, and 81 normal controls, evaluating complement parameters, spontaneous plasma kallikrein activity, the capacity of plasma to inhibit exogenous kallikrein activity, and cleavage of high‐molecular‐weight kininogen (HK). Sixty‐five HAE‐C1‐INH patients were screened for mutations in the C1‐INH gene. Results As expected, plasma C1‐INH levels and activity and C4 levels were low in the HAE‐C1‐INH patients. Spontaneous plasma kallikrein activity in patients in remission was higher than in controls (P = 0.001) and increased during acute attacks (P = 0.01), whereas the capacity of inhibiting kallikrein activity was lower in patients in remission than in controls (P = 0.001) and further reduced during attacks (P = 0.001). HAE‐C1‐INH patients in remission had higher levels of cleaved HK than controls (P = 0.001), and these further increased during acute attacks (P = 0.001). Cleaved HK levels were higher in highly symptomatic HAE‐C1‐INH patients than in those with less frequent attacks (P = 0.001). Thirty‐five different mutations in the C1‐INH gene were equally distributed in patients with different attack frequencies. Conclusions Measuring plasma levels of cleaved HK may be a sensitive mean of assessing disease severity in HAE‐C1‐INH patients.